Deletion of p75NTR rescues the synaptic but not the inflammatory status in the brain of a mouse model for Alzheimer’s disease - Demuth, Hendrik; Hosseini, Shirin; Düsedeau, Henning Peter; Dunay, Ildiko Rita; Korte, Martin; Zagrebelsky, Marta (Frontiers in Molecular Neuroscience, 2023)
Alzheimer’s disease (AD), is characterized by a gradual cognitive decline associated with the accumulation of Amyloid beta (Aβ)-oligomers, progressive neuronal degeneration and chronic neuroinflammation. Among the receptors shown to bind and possibly transduce the toxic effects of Aβ-oligomers is the p75 neurotrophin receptor (p75NTR). Interestingly, p75NTR mediates several crucial processes in the nervous system, including neuronal survival and apoptosis, maintenance of the neuronal architecture, and plasticity. Furthermore, p75NTR is also expressed in microglia, the resident immune cells of the brain, where it is markedly increased under pathological conditions. These observations indicate p75NTR as a potential candidate for mediating Aβ-induced toxic effects at the interface between the nervous and the immune system, thereby potentially participating in the crosstalk between these two systems. Here we used APP/PS1 transgenic mice (APP/PS1tg) and compared the Aβ-induced alterations in neuronal function, chronic inflammation as well as their cognitive consequences between 10 months old APP/PS1tg and APP/PS1tg x p75NTRExonIV knockout mice. Electrophysiological recordings show that a loss of p75NTR rescues the impairment in long-term potentiation at the Schaffer collaterals in the hippocampus of APP/PS1tg mice. Interestingly, however loss of p75NTR does not influence the severity of neuroinflammation, microglia activation or the decline in spatial learning and memory processes observed in APP/PS1tg mice. Together these results indicate that while a deletion of p75NTR rescues the synaptic defect and the impairment in synaptic plasticity, it does not affect the progression of the neuroinflammation and the cognitive decline in a mouse model for AD.